Blood in the water: DNA barcoding of traded shark fins in Singapore - Drescher, Lynn; Heng, Noel Jin Kiat; Chin, Min Yi; Karve, Neel R. O.; Cheung, Edward Jun Wei; Kurniadi, Anastasia; Urera, Mariana Quesada; Waldeck, Felipe Gabriel; Dharshini, U.; Hoe, Nirel Tze En; Choo, Joshua Song Yang; Lok, Russell Fock Jun; et al. (Frontiers in Marine Science, 2022)
Overfishing has significantly decreased global shark populations, with some species experiencing reductions of approximately 70% over the last 50 years. Singapore is a major shark fin transhipment hub that helps to satisfy the global demand for shark fins, which are considered status symbols and reputed to have medicinal value in Asian culture. Despite the recognised and urgent need to better protect shark populations, the success of such efforts has been limited by the difficulties associated with visually identifying the species of shark from which the fins originated. In this study, we collected 451 shark fin tissue samples from a variety of local retail markets in Singapore. Using DNA barcoding techniques, we amplified a 350 base pair fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene from each to identify the species sold in Singapore. We identified 22 shark species, of which 17 are categorised as Threatened (Critically Endangered, Endangered or Vulnerable) under the IUCN Red List. Six of these species are also listed on Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES).